Leptospirose genital experimental crônica com estirpes autóctones de Leptospira santarosai do sorogrupo Sejroe - Rocha, B. R.; Balaro, M. F. A.; Pereira, P. V.; Martins, G.; Lilenbaum, W. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis in livestock is usually a chronic infection that leads to reproductive problems. Few studies succeeded on reproducing the chronic genital infection on experimental conditions. Objective: To assess the chronic experimental genital leptospirosis with Leptospira santarosai strains of serogroup Sejroe.